Profil Status Gizi Penderita Tuberkulosis Paru-Multi Drug Resistance dengan Diabetes Mellitus Tipe 2 di RSUD Dr. Soetomo Surabaya Tahun 2016 : [Nutritional Status of Multidrug-Resistant Tuberculosis Patient with Diabetes Mellitus Type 2 in Dr. Soetomo General Hospital Surabaya] - Mega Rizkya Arfiana; Tutik Kusmiati; Jongky Hendro Prayitno (Jurnal Respirasi, 2018)
Background: Indonesia is the third highest country of Tuberculosis (TB) prevalence world wide. Beside resistances, factor that being a burden for control TB is comorbidities, such as Diabetes Mellitus Type 2 (DMT2). This research aimed to determine the Nutritional Status of Multi Drug Resistance Tuberculosis (MDR-TB) with DMT2 Patients. Methods: This is a descriptive retrospective study observing Nutritional Status of MDR-TB with DMT2 patients based on gender, age, weight, height, and Fasting Blood Glucose (FBG) registered since January,1st –December, 31th 2016 in RSUD Dr. Soetomo Surabaya. Results: Out of 42 Samples, there are 20 mens and 22 womens suffer MDR-TB with DMT2. The Nutritional Status of Women is Normal (28.57 %) and Man is Underweight (16.6 %). Based on the age of patients, 51-60 years is the highest frequency. The mean of Body Mass Index (BMI) from all age categories are Normal, except 31-40 years. The mean of height is 159.95 cm and weight is 52.88 kg. In FBG’s category, 100-200 is the highest frequency and mostly has normal BMI. The mean of BMI is 20.51 kg/m2. Conclusion; Majority patients of MDR-TB with DMT2 has Normal BMI.